A meta-analysis on the effectiveness of the stem approach on students’ mathematical creative thinking ability - Rahmawati, Laili; Juandi, Dadang; Nurlaelah, Elah (Universitas Islam Raden Intan Lampung, INDONESIA, 2023)
Studies on the effectiveness of STEM implementation in Mathematics learning, especially in mathematical creative thinking ability carried out by previous researchers, are interesting to be studied. However, several studies have shown different results that can lead to different interpretations. This study aims to estimate dan examine the effectiveness of STEM on students' mathematical creative thinking ability from the relevant studies. This study analyzed 12 primary studies from various electronic search engines within the year of publication from 2017 to 2022. All primary studies in this research were analyzed using the meta-analysis with Comprehensive Meta-Analysis 3.0 (CMA 3.0) software by selecting the formula of Hedge to determine its effect size. The results of this meta-analysis study indicated that the STEM approach was effective for students' mathematical creative thinking abilities with an effect size of 0,935 in the category of high effect. There were differences in the effect size of the STEM approach on students' mathematical creative thinking abilities regarding STEM integration with learning models and educational levels. This means that the type of integration of the STEM approach with the learning model and educational level significantly causes heterogeneity in students' mathematical creative thinking abilities. The results of this study are expected to provide educators with an overview of how STEM can be applied in mathematics learning, especially in improving mathematical creative thinking ability.